2021
DOI: 10.1177/02692163211026516
|View full text |Cite
|
Sign up to set email alerts
|

How can we ensure the success of specialised palliative home-care? A qualitative study (ELSAH) identifying key issues from the perspective of patients, relatives and health professionals

Abstract: Background: Specialised palliative home-care supports patients with life-limiting diseases in their familiar surroundings. The number of palliative care teams and patients being cared for is increasing worldwide. To assess and improve quality, it is needed to understand, how specialised palliative home-care can be provided successfully. For this purpose we examined the views of all involved stakeholders. Aim: To identify the issues that patients, their relatives and involved health professionals view as import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Nurses in palliative care should be given the opportunity to identify those individuals who have an increased risk of suicide attempts. Involving close relatives with knowledge about the individual's thoughts and feelings can be valuable (Seipp et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses in palliative care should be given the opportunity to identify those individuals who have an increased risk of suicide attempts. Involving close relatives with knowledge about the individual's thoughts and feelings can be valuable (Seipp et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by demonstrating empathy when broaching sensitive topics, health professionals can reduce burden and scepticism. A predefined framework ensures comparability and orientation, but a successful SOPC approach requires flexibility and the ability to adapt to individual needs and situations [ 12 ]. Health professionals in other studies also feared that the use of PROMs may reduce the quality of relationships, but they also found that PROMs can result in open conversations and help patients raise topics of personal relevance [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…We purposively sampled the SOPC teams for team location (rural and urban locations), and the use of differing EDS, to address software-related issues with regard to the expansion in all hessian teams. The SOPC teams knew the research team from a previous phase of the study [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a first step, we examined key features of successful care from the perspective of patients, relatives and health professionals. We found that 'treatment of complex symptoms, comprehensive care and a sense of security, as well as a focus on the quality of relationships, respect for individuality and the facilitation of self-determination' [22] are relevant topics that need to be covered. On this basis, we assembled a set of validated outcome measures, which is based on the Outcome Assessment and Complexity Collaborative (OACC) suite of measures [6].…”
Section: Introductionmentioning
confidence: 99%